2013
DOI: 10.1371/annotation/90602bc3-5052-49ac-a7fb-33210d7c8b4d
|View full text |Cite
|
Sign up to set email alerts
|

Correction: MicroRNA-17-92, a Direct Ap-2α Transcriptional Target, Modulates T-Box Factor Activity in Orofacial Clefting

et al.

Abstract: Among the most common human congenital anomalies, cleft lip and palate (CL/P) affects up to 1 in 700 live births. MicroRNA (miR)s are small, non-coding RNAs that repress gene expression post-transcriptionally. The miR-17-92 cluster encodes six miRs that have been implicated in human cancers and heart development. We discovered that miR-17-92 mutant embryos had severe craniofacial phenotypes, including incompletely penetrant CL/P and mandibular hypoplasia. Embryos that were compound mutant for miR-17-92 and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…For example, Ling Li found that the negative feedback loop between E2F1 and miR-17-92 may contribute to palatal development by regulating the proliferation and cell cycle of palatal mesenchymal cells (Li et al, 2017). It has been reported that mutation of miR-17-92 often leads to a severe craniofacial phenotype by targeting the Bmp/AP-2α-miR-17-92-Tbx pathway (Wang et al, 2013). Our previous study found that the miR-146a rs2910164 G allele was associated with the expression of miR-146a, which contributed to the occurrence of oral cleft by regulating TRAF6 expression (Pan et al, 2018).…”
Section: Introductionmentioning
confidence: 94%
“…For example, Ling Li found that the negative feedback loop between E2F1 and miR-17-92 may contribute to palatal development by regulating the proliferation and cell cycle of palatal mesenchymal cells (Li et al, 2017). It has been reported that mutation of miR-17-92 often leads to a severe craniofacial phenotype by targeting the Bmp/AP-2α-miR-17-92-Tbx pathway (Wang et al, 2013). Our previous study found that the miR-146a rs2910164 G allele was associated with the expression of miR-146a, which contributed to the occurrence of oral cleft by regulating TRAF6 expression (Pan et al, 2018).…”
Section: Introductionmentioning
confidence: 94%
“…These findings suggest that the TBX1–miR-200b/200a/429 and miR-203–ZEB2 loop is important for epithelial cell differentiation, EMT, and stemness in the palatal epithelium, and their dysregulation results in CL/P. Indeed, miR-17-92 null mice ( miR-17-92 -/- , miR-17-9 -/- ;miR-106b-25 +/- , and miR-17-92 -/- ;miR-106 -/- mice) display CLP through upregulation of Tbx1 , Tbx3, Fgf10, Shox2, and Osr1 expression [ 101 ]. On the other hand, overexpression of the miR-17-92 cluster suppresses expression of E2F1 , a transcription factor, and inhibits cell proliferation through dysregulation of the cell cycle in mouse embryonic palatal mesenchymal (MEPM) cells [ 102 ].…”
Section: Micrornas Related To Cleft Palatementioning
confidence: 99%
“…The expression of this gene is upregulated in cutaneous basal cell carcinoma, inversely to miR-451a [ 49 ]. miR-17-92 fine-tunes the expression of Tbx1 in craniofacial development, suggesting miR-17-92 as a candidate genetic modifier for Tbx1 [ 50 ]. Thus, miRNAs both inside and outside the 22q11.2 locus may influence the severity of the clinical phenotypes of DGS/VCFS.…”
Section: Genetics Of Dgs/vcfsmentioning
confidence: 99%